Влијанието на нивото на јазична компетенција врз изборот на стратегии во усвојување странски јазици - Николовска Анжела (Образовни рефлексии, 2019)
The aim of this paper is to cast light on the correlation between language proficiency and the choice of language learning strategies by reviewing the findings of the relevant studies in this area. It transpired from the research that learners at a higher proficiency level use a richer repertoire of language learning strategies. Cognitive strategies are the most frequently used. However, it remains unclear whether language proficiency influences the choice of language learning strategies or language learning strategy use determines the proficiency level. Finally, the relevant teaching implications are discussed in light of the literature review.
Keywords: language proficiency, research, language learning strategies, correlation, teaching implications